Analisis SPK Penerima Bantuan Rumah Tidak Layak Huni Menggunakan Metode MABAC di Kota Jambi: Analysis of Decision Support System Design for Uninhabitable House Assistance Recipients Using the MABAC Method in Jambi City - Noviana, Risma Dwi; Jasmir; Joni Devitra (LPPM Universitas Dinamika Bangsa, 2025)
The Jambi City Housing and Settlement Areas Office in processing data for receiving uninhabitable housing assistance is still using Microsoft Excel. So that there is a problem, namely there are many houses that are classified as Uninhabitable Houses (RTLH) in Jambi City, and determining which ones are eligible for assistance and which ones are not is a time-consuming task and requires proper assessment and errors in assessment can have a bad impact on the efficiency of budget use and inequality in the distribution of aid. Therefore, this study aims to provide a solution to the problems that occur by offering a system to support the decision to receive uninhabitable housing assistance using the MABAC method where the author develops a system with a prototype method and uses a unified model language system model approach using usecase diagrams, activity diagrams, class diagrams and flowcharts. So that the results of the application can be used by can provide the convenience of choosing a decent assistance receipt quickly and precisely.